Importance of tides for periastron precession in eccentric Neutron Star-White Dwarf Binaries - Sravan, N. (2014)
Although not nearly as numerous as binaries with two white dwarfs, eccentric neutron star–white dwarf (NS–WD) binaries are important gravitational-wave (GW) sources for the next generation of space-based detectors sensitive to low frequency waves. Here we investigate periastron precession in these sources as a result of general relativistic, tidal, and rotational effects; such precession is expected to be detectable for at least some of the detected binaries of this type. Currently, two eccentric NS–WD binaries are known in the galactic field, PSR J1141−6545 and PSR B2303+46, both of which have orbits too wide to be relevant in their current state to GW observations. However, population synthesis studies predict the existence of a significant Galactic population of such systems. Though small in most of these systems, we find that tidally induced periastron precession becomes important when tides contribute to more than 3% of the total precession rate. For these systems, accounting for tides when analyzing periastron precession rate measurements can improve estimates of the inferred WD component mass and, in some cases, will prevent us from misclassifying the object. However, such systems are rare, due to rapid orbital decay. To aid the inclusion of tidal effects when using periastron precession as a mass measurement tool, we derive a function that relates the WD radius and periastron precession constant to the WD mass.